2022
DOI: 10.31234/osf.io/7j26y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Misleading count: An identity-based intervention to counter partisan misinformation sharing

Abstract: Given the spread of partisan misinformation in politically polarized environments, it is critical to develop interventions that are effective at reducing misinformation sharing in these contexts. Across three online experiments with liberals and conservatives in the U.S. and the UK, we found that crowdsourced accuracy judgments in the form of a Misleading count were effective in reducing participants’ likelihood of sharing misinformation, especially when these judgements reflected an in-group’s opinion (versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…In line with this, experimental studies have found that providing social rewards for sharing high-quality content and punishments for sharing low-quality content 77 improves the quality of news people report intending to share. Additionally, making people publicly endorse that the news that they share is accurate 78 , or showing people that fellow in-group members believe content is misleading 79 , also improves people's sharing intentions. Future work should continue to explore how to incentivize people to engage with more accurate content online by, for example, emphasizing social norms around accuracy or emphasizing the reputational benefits of sharing accurate content (as in experiment 4).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, experimental studies have found that providing social rewards for sharing high-quality content and punishments for sharing low-quality content 77 improves the quality of news people report intending to share. Additionally, making people publicly endorse that the news that they share is accurate 78 , or showing people that fellow in-group members believe content is misleading 79 , also improves people's sharing intentions. Future work should continue to explore how to incentivize people to engage with more accurate content online by, for example, emphasizing social norms around accuracy or emphasizing the reputational benefits of sharing accurate content (as in experiment 4).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, interventions based on in-group norms have been found to decrease willingness to fight and die in defense of sacred values in devoted actors (Hamid et al, 2019). When it comes to misinformation, interventions and platform features that appeal to identity and group-based norms might be more effective than identity-neutral alternatives for extreme partisans (Pretus et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This section starts with a review article on punishment as a bottom-up means of norm enforcement across cultures and societies [31]. It proceeds with four research articles that design and test norm interventions to change behavioural intentions in both online [32] and offline settings and in different cultural contexts [33], for norms and meta norms [29], to assess both individual and welfare consequences [30].…”
Section: (C) Engineering Norm Change For Behavioural Changementioning
confidence: 99%
“…Recent studies show that the success of accuracy-nudging interventions, which are among the most popular approaches to combating misinformation, is relatively weak, especially when the issue is politically polarized. Pretus et al [32] conduct three experiments in the USA and in the UK and find that exposing individuals to normative accuracy judgements by their in-group (versus general others) reduces the likelihood that they will share inaccurate information about partisan issues by 25% (compared to a control condition).…”
Section: (C) Engineering Norm Change For Behavioural Changementioning
confidence: 99%
See 1 more Smart Citation